IMPLEMENTATION OF SIMPLE ADDITIVE WEIGHTING TO DETERMINE THE BEST EMPLOYEES IN THE CAMAT TINGGI RAJA OFFICE - Cindy Eka Putri; Havid Syafwan; Muhammad Ihsan (Kresnamedia Publisher, 2022)
Decision-making for the best employees in Camat Tinggi Raja Tinggi Office requires objective and transparent considerations to select the best employees. This study aimed to apply the Simple Additive Weighting (SAW) method to determine the best employees in Camat Tinggi Raja Tinggi Office. This research method used quantitative methods. The data collected was in the form of employee data of the Raja Tinggi Subdistrict Office in the form of names, attitudes, work discipline, loyalty, responsibilities, and task completion. Data were analyzed using the SAW method based on preference values. The results showed that the employee with the name S had the highest preference value, 0.88. This research concludes that the SAW method decides the best employee in Camat Tinggi Raja Tinggi Office, namely the employee with the name S